ANALISIS CARA PENANGANAN DENGAN KEJADIAN INFEKSI SALURAN KEMIH PADA PASIEN DI POLIKLINIK UROLOGI RSUD DR M YUNUS BENGKULU - Liza Fitri Lina; Ferasinta Ferasinta; Eva Oktavidiati; Dwi Puji Lestari (Jurnal Surya Muda, 2019)
Urinary tract infection is a pathological condition that has been very long known and can be found in various primary health care to subspesialistik. The purpose of this study is to analyze the handling aspect with urinary tract infections in patients in urology clinic RSUD Dr.. M Yunus Bengkulu. The research design used was qualitative with descriptive approach. Informant research method in this research using technique "Purposive Sampling". The source of information in this study is the patients who visited the urology clinic RSUD Dr.. M Yunus Bengkulu who is married and data from medical record of urology clinic RSUD Dr. M Yunus Bengkulu as many as 5 patients. The data collection using in-depth interview technique. The results of this study obtained by 2 theme that is handling aspect. In the handling aspect, the patient has done the examination in urology clinic of RSUD Dr. M Yunus Bengkulu and has run the treatment so that it is feeling healthy. The conclusions obtained in this study are; Informants understand little about urinary tract infections, all new informants first experience urinary tract infections.